Remote sensing in urban sprawl modelling: scenario and way forward in developing countries (UP 040) - Mohd. Noor, Norzailawati; Abdullah, Alias (2011)
In recent years, the developing countries was deal the use of computer based models of land use changes and urban sprawl which have greatly increased and tend to become important tools in supporting urban planning and management. The modeling recently used in various planning specialization such as economics, transportation, spatial planning, urbanization, ecology, and other social science aspects. However, modeling sprawl phenomena which convergence to remote sensing data has not fully demonstrated lack of common ground and testable concepts. Remote sensing data products have often been incorporated into urban modeling applications as additional sources of spatial data primarily for historical land use history. The objectives of this study to identify recent scenario and way forward of remote sensing tools in urban sprawl modeling based on review of previously studied and urban planning situation in developing countries and Malaysia contexts specifically.